posted by Kathy .
2a^2 + 6ab^2-12a^2b^3 divided by 24ab
-2a^2/-24ab + 6ab^2/24ab--12a^2b^3/24ab=
-12ab^2 +12a +4b
-2a^2 / 24ab is not -12ab
It is -a/12b
because you have -(2a)(a) / (2a)(12b)
and the 2a's cancel
6ab^2/24ab = (6ab)(b) / (6ab)(4) = b/4
12a^2b^3 / 24ab = (12ab)(ab^2) / (12ab)(2) = ab^2/2
Looks like you have some serious practice ahead. You can enter your expressions in wolframalpha.com to check your answers.
Be sure to watch how it interprets your input, and use extra parentheses as needed!